Tânia and Graziela De Castro Saraiva: affective records of the history of puppet theater in Rio Grande do Sul (Móin-Móin Magazine - Studies in the Art of Puppetry, 2020)
This text is about the record of the work of sisters Tânia e Graziela de Castro Saraiva in structuring of puppet theater in the state of Rio Grande do Sul, Brasil. From the methodology of life story, were collected that embody memories, events and affections. Based on this material, its presented the developments form the stories of Tânia and Graziela, as well as the views of different professionals in the field on the actions and creations of the two sisters, and the registration of the Associação Gaúcha de Teatro de Bonecos (AGTB).